2015
DOI: 10.1007/s11912-015-0479-4
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Therapeutic Targets for Male Germ Cell Tumors

Abstract: Male germ cell tumors (GCTs) are curable cancers, yet 10-15 % of patients with metastatic disease fail cisplatin-based first-line treatments. While therapeutic options have increased for various other cancers, little progress has been made in the management of GCT in the last decades. A better understanding of the molecular alterations underlying the disease and identification of new therapeutic targets are needed. Several phase I/II studies with promising new agents are ongoing or have been completed, but mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…However, spermatocytes and spermatids were the main cell types that expressed PD-L1 in the seminiferous tubules in an allograft study. 32 In addition, recent data showed that there was little or no PD-L1 expression, 33,34 and PD-1 expression was also not detected in normal human testes. 34 This ambiguity surrounding expression made it difficult to identify the exact function of the PD-1/PD-L1 pathway in testicular functions.…”
Section: Secco Et Al 31 Reported That Murine Scs Inducibly Express Pd-l1mentioning
confidence: 99%
See 2 more Smart Citations
“…However, spermatocytes and spermatids were the main cell types that expressed PD-L1 in the seminiferous tubules in an allograft study. 32 In addition, recent data showed that there was little or no PD-L1 expression, 33,34 and PD-1 expression was also not detected in normal human testes. 34 This ambiguity surrounding expression made it difficult to identify the exact function of the PD-1/PD-L1 pathway in testicular functions.…”
Section: Secco Et Al 31 Reported That Murine Scs Inducibly Express Pd-l1mentioning
confidence: 99%
“…32 However, controversial results were obtained in human testes. Based on immunohistochemical staining, researchers claimed that there was no 33 Complete spermatogenesis is established in the testes of adult mice.…”
Section: Until Recently Only Two Studies Have Reported No Detectablementioning
confidence: 99%
See 1 more Smart Citation
“…The associated toxicity should be taken into consideration [ 64 ]. Frankhauser et al found that the expression of PD-1 and PDL-1 were high in GCTs which may bring insight to immune checkpoint inhibitor treatment [ 65 ]. A previous report suggested that a disseminated platinum refractory non-seminomatous GCTs showed response with tumor marker decline after initiating off-label nivolumab; however the patient had new brain metastasis 5 months later [ 66 ].…”
Section: Pediatric Extracranial Germ Cell Tumormentioning
confidence: 99%
“…In general, the common mutations in oncogenes and tumor suppressors that are observed in other tumor types are relatively rare in testicular cancers and among the potentially targetable genomic alterations that have been identi ed, such as mutations in the FGFR, AKT and PIK3CA genes, it is unclear what role these might play in the development of chemoresistance, if any. 28 Some progress is being made in certain types of testicular cancer and several di erent treatment strategies continue to be evaluated. Among those drugs that look promising in early-stage clinical testing are cyclin-dependent kinases 4 and 6 (CDK4/6) inhibitors.…”
Section: Figurementioning
confidence: 99%